Analyzing stability of protective structures as the elements of geotechnical tailing pond saf - Tymoshchuk, Vasyl; Тимощук, Василь; Rudakov, Leonid; Рудаков, Леонід; Pikarenia, Dmytro; Пікареня, Дмитро; Orlinska, Olha; Орлінська, Ольга; Hapich, Hennadii; Гапіч, Генадій (Національний гірничий університет України, 2023)
Purpose is the assessment of soil retaining wall stability to ensure geotechnical safety during the radioactive waste tailing pond closure and further recultivation (or rehabilitation) in Kamianske town (Ukraine). Methods. Geomechanical stability of the protective structure has been assessed relying upon the analysis of geological-hydrogeological, engineering-geological, and geotechnical conditions of the certain tailing pond area using a deformation elastic-plastic model of a medium implemented on the basis of finite-element method. For the purpose, the dam slopes have been detalized taking into consideration their geometry as well as changes in vertical section of rock material characteristics in accordance with the earlier geophysical studies; exploration drilling; and engineering-geological surveys. Findings. Stability coefficients of protective tailing pond dam have been identified within the typical areas of a hydraulic structure; it provides high reliability and representativeness of the whole structure health in time as well as under various conditions of the industrial waste water saturation. It has been defined that the stability coefficients varies from ks = 1.372 to 4.758. Comparison of the indicators between 2022 and 2016 demonstrates a tendency of the slope stability coefficient decrease due to water saturation and groundwater level rise. Nevertheless, design characteristics of the structure make it possible to ensure satisfactory a stability coefficient along the whole dam length being 1.13 times higher than the standard one (i.e. ks = 1.250). Originality. The dependence of the tailing pond protective dam stability upon a water supply degree at the forecasted groundwater level rise at the expense of atmospheric and melt water ingress to the tailing pond has been defined. The danger of complete radioactive waste water saturation is a significant reduction in the stability coefficient of the protective structure, which can be supported by predictive modelling data. If strength parameters of a dam material decline for the most critical area then the strength coefficient decreases starting from 1.532 in terms of the current groundwater level down to 1.372 as for the forecasted dam water supply. The figure is more than 10% of its initial stability. Practical implications. The obtained results substantiate the necessity; moreover, they are of practical value while improving hydrological, hydrogeological, and geotechnical monitoring of the analyzed tailing pond to ensure its radiation safety under different conditions of further behaviour during closure, recultivation, or rehabilitation.Мета. Оцінка стійкості ґрунтової огороджувальної дамби для забезпечення радіаційної та екологічної безпеки під час закриття і подальшої рекультивації (або реабілітації) хвостосховища радіоактивних відходів (м. Кам’янське, Україна). Методика. Оцінка геомеханічної стійкості огороджувальної споруди виконана на онові аналізу геолого-гідрогеологічних, інженерно-геологічних та геотехнічних умов ділянки хвостосховища з використанням деформаційної пружно-пластичної моделі середовища, реалізованої на базі методу скінченних елементів. Для цього виконана деталізація укосів дамби з урахуванням їх геометричних розмірів та змін в вертикальному перерізі властивостей породного матеріалу згідно з даними попередньо виконаних геофізичних досліджень, розвідувального буріння та інженерно-геологічних вишукувань. Результати. На характерних ділянках гідротехнічної споруди встановлені коефіцієнти стійкості укосів огороджувальної дамби хвостосховища. Це забезпечує високу достовірність і репрезентативність результатів для прогнозування зміни технічного стану всієї споруди у часі та за різних умов водонасичення промислових відходів. Визначено, що коефіцієнти стійкості змінюються в межах від ks = 1.372 до 4.758. Порівняння цих показників у 2022 році з параметрами, визначеними у 2016 році, засвідчують тенденцію зниження коефіцієнтів стійкості укосів внаслідок водонасичення та підвищення рівня ґрунтових вод. Проте, конструктивні характеристики споруди надають змогу забезпечити відповідний коефіцієнт стійкості по всій довжині дамби в межах, що перевищує нормативний (ks = 1.250) в 1.1-3.0 рази. Наукова новизна. Встановлена залежність стійкості огороджувальної дамби хвостосховища від ступеня обводнення дамби при прогнозованому піднятті рівня ґрунтових вод за рахунок надходження до хвостосховища атмосферних і талих вод. Небезпека повного водонасичення радіоактивними відходами полягає у суттєвому зниженні коефіцієнту запасу стійкості огороджувальної споруди, що підтверджується даними прогнозного моделювання: при зниженні параметрів міцності матеріалу дамби для найбільш критичної ділянки значення коефіцієнту запасу стійкості зменшується від 1.532 при існуючому положенні рівня ґрунтових вод до 1.372 при прогнозованому обводненні дамби, тобто більш ніж на 10% від її початкової стійкості. Практична значимість. Отримані результати обґрунтовують необхідність та мають практичне значення при вдосконаленні гідрологічного, гідрогеологічного та геотехнічного моніторингу досліджуваного хвостосховища для забезпечення його радіаційної безпеки за різних умов подальшого поводження під час закриття, рекультивації або реабілітації.
Дослідження стійкості огороджувальних споруд як елементів екологічної безпеки хвостосховищ
Keywords: tailing pond; хвостосховище; environmental safety; екологічна безпека; radiation safety; радіаційна безпека; protective dam; огороджувальна дамба